188 Taking a safe system approach to eliminate child road traffic deaths. (20th November 2022) - Harris, Anne; Murphet, Blaise; Wilson, Kylie
Abstract : Context: Road trauma is the leading cause of death for children in Australia aged 1–14 years, and globally between the age of 5–29 years. In the five year period between 2015 – 2019, more than 8, 600 children and young people aged 0–25 years were killed or seriously injured on the roads in Victoria, Australia. In light of the unacceptable levels of child road trauma, there is a need to consider and implement the most effective measures to proactively work towards a future where we eliminate child deaths on the roads. Purpose: This paper builds upon a series of studies commissioned by the Transport Accident Commission of Victoria that investigate international best practice and the impact and effectiveness of how policy and behavior change interventions delivered in coordination through a Safe System Approach could potentially eliminate child road deaths in Victoria. It outlines the importance of addressing school road safety holistically, through the combination of road safety education and school zone infrastructure improvements and describes the key policy and behavioural initiatives that are recognized as best-practice in preventing road trauma among school communities. Analysis: The paper builds upon this research to present a series of policy and programmatic considerations for school zone improvements that could be adopted to reduce travel speed and improve co-benefits such as healthy lifestyles, and it presents considerations based on detailed forecasting to ascertain whether the elimination of child road trauma is possible through a coordinated safe system approach.